Report of the Working Group on Vocational Agricultural Education - Planning Commission (Planning Commission Government of India, 1968)
The Report of the Working Group on Vocational Agricultural Education outlines a strategic framework for enhancing agricultural education in India. Targeting youth aged 14 and above, the initiative emphasizes practical skills, community-relevant curricula, and interdisciplinary learning delivered primarily in regional languages. Qualified teachers with specialized training will lead programs in rural institutes, agricultural colleges, and secondary schools, with phased implementation starting from 300 centers by 1971. Projected enrollments are expected to grow from 500 students in 1968 to 21,000 by 1973, with a total cost of Rs. 13.51 million. Collaborative oversight by the Ministry of Agriculture, the Ministry of Education, and a Central Board is proposed, alongside continuous practical evaluation and cooperative programs like Future Farmers of India. The report underscores vocational agricultural education as essential for improving rural livelihoods and enhancing national agricultural productivity.
Government of India Planning Commission New Delhi
Keywords: Vocational Agricultural Education; Practical Skills; Youth Training; Curriculum Design; Teacher Qualifications; Rural Institutes; Agricultural Colleges; Enrollment Projections; Regional Languages; Ministry of Agriculture; Central Board; Cooperative Programs